Analysis of the Italian football in the 2016 European football championship - Kurak, K.; Büyükçelebi, H.; Açak, M. (European Journal of Physical Education and Sport Science, 2021)
The 15th European Football Championship (UEFA) was hosted by France. Italy exhibited a different football from this previous tournament. Italy participated in the European Football Championship 8 times, played three finals and won this trophy in 1968. Before 2016, Italian football is a team that has adopted the strict defense principle. It is aimed to reach the result based on standing balls and individual actions. With the 5-4-1 and 4-5-1 game system, the defense is not at risk and few players are attacked. In the preference of players, players with good defense power are preferred. In EURO 2016, Italy football; Looking at the comments from around the world, it has changed the style and style of the game. It is seen that it applies new trends in football. We can summarize some of these trends as follows; there is a very tactically trained team that can play different systems. Different game systems have been applied in different matches. It was observed that they wanted to direct the game by owning the ball. When they lost the ball, oppression was set up instead of waiting for the opponent to make mistakes. Distance between locations has been established as 35-40 m. Instead of waiting behind the ball, the opponent was directed to the press area to create pressure against the ball. These situations caused the Italian football team to play an attractive football.